2022
DOI: 10.3390/jpm12101707
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting EfficientNet, ViT, and gMLP for COVID-19 Detection in Ultrasound Imagery

Abstract: A timely diagnosis of coronavirus is critical in order to control the spread of the virus. To aid in this, we propose in this paper a deep learning-based approach for detecting coronavirus patients using ultrasound imagery. We propose to exploit the transfer learning of a EfficientNet model pre-trained on the ImageNet dataset for the classification of ultrasound images of suspected patients. In particular, we contrast the results of EfficentNet-B2 with the results of ViT and gMLP. Then, we show the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Therefore, they have been used in many recent medical image AI studies. 21 23 Our model using EfficientNet showed a good classification performance for microscopic images, and we look forward to future research in this area.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, they have been used in many recent medical image AI studies. 21 23 Our model using EfficientNet showed a good classification performance for microscopic images, and we look forward to future research in this area.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, it does not address the end-to-end video classification of an LUS clip. Eventually, the literature retains a final study [ 15 ] that compared a Multi-Layer Perceptron (MLP) network, the EfficentNet and the Vision Transformer (ViT). The study found that the EfficientNet outperforms the other techniques measuring 96% accuracy.…”
Section: Introductionmentioning
confidence: 99%